Campesinato, agroecologia e convivência com o semiárido em Solânea-PB - Silva, Pablo Melquisedeque Souza e (2013)
This research focuses primarily study the organization of peasant production in the city of Solânea-PB, especially the role of agroecology and coexistence with the semiarid in the process of reproduction. For its realization we used secondary data that had the IBGE, INCRA, Polo Sindical da Borborema and AS-PTA as a source. Primary data were collected during field work, which were divided into several times. With scripts structured and / or semi-structured, were interviewed 70 farmers responsible for agricultural establishments and householders, and leaders of the STR, AS-PTA, the Polo Sindical da Borborema of ONGIFA, among others. During the research, were recorded events and training activities and mobilization performed by agents that promote agroecology and the peasantry in Solânea and Agreste paraibano. The trajectory of this research provided to verify the peasantry of the city of Solânea, its organization, its partners, the use of agro-ecology and strategies for coexistence with the semiarid. Agents such as AS-PTA, ONGIFA, ASA, Polo Sindical da Borborema, UFPB, among others who have worked so centered on family and peasant production by agroecological bias, presented as crucial for the strength, the permanence and recreation planning peasant. Through the dissemination of agroecological practices, integration of peasants in solidarity networks, the provision of technical training courses and citizen, these organisms have obtained important results in the retention of the man in the field, protecting the environment, in coexistence with the semiarid and consolidating the territory of Hope in Solânea. The analysis performed allows us to affirm that there is a form of peasant production in the city of Solânea, historically formed, and that she has endured and expanded agroecological perspective